2022
DOI: 10.1088/1748-9326/ac9aca
|View full text |Cite
|
Sign up to set email alerts
|

Carbon flux estimates are sensitive to data source: a comparison of field and lab temperature sensitivity data

Abstract: A large literature exists on mechanisms driving soil production of the greenhouse gases CO2 and CH4. Although it is common knowledge that measurements obtained through field studies vs. laboratory incubations can diverge because of the vastly different conditions of these environments, few studies have systematically examined these patterns. These data are used to parametrize and benchmark ecosystem- to global-scale models, which are then susceptible to the biases of the source data. Here, we examine how green… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 101 publications
0
9
0
Order By: Relevance
“…Results can be affected by experimental protocols (X. Chen et al., 2010) as well as experiment length (Birge et al., 2015; Hamdi et al., 2013). Extrapolating such results to in situ conditions, or using them to parameterize models, must be done with caution (J. Chen et al., 2023; Patel et al., 2022).…”
Section: Laboratory Incubations and Mesocosmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Results can be affected by experimental protocols (X. Chen et al., 2010) as well as experiment length (Birge et al., 2015; Hamdi et al., 2013). Extrapolating such results to in situ conditions, or using them to parameterize models, must be done with caution (J. Chen et al., 2023; Patel et al., 2022).…”
Section: Laboratory Incubations and Mesocosmsmentioning
confidence: 99%
“…Extrapolating such results to in situ conditions, or using them to parameterize models, must be done with caution (J. Patel et al, 2022).…”
Section: Laboratory Incubations and Mesocosmsmentioning
confidence: 99%
“…The remaining points are obtained from the so-called 𝑄𝑄 10 model [55], as in Koutsoyiannis et al [30 (Appendix A.1)]. This is based on the equation:…”
Section: Premises Of the Applicationmentioning
confidence: 99%
“…We found that both incubation and chloroform extraction methods of estimating microbial biomass C produced similar ∆ 14 C results in the upper 50 cm soil increment, indicating that for these surface soils, either method could be used to assess microbially used C. In contrast, the ∆ 14 C values for soil collected from below 50 cm from the two methods diverge. It is possible that the soil sampling process and sample handling prior to incubation released fresh, labile C that otherwise would not have been accessible for decomposition (Salomé et al 2010, Herbst et al 2016, Schädel et al 2020, Patel et al 2022. Alternatively, the 14 C depleted biomass values in the deeper soils may reflect non-living cell material that was liberated by the chloroform biomass extraction.…”
Section: Comparison Of Biomass Extraction and Laboratory Incubation M...mentioning
confidence: 99%
“…Given the importance of microbial SOC cycling, many studies use laboratory soil incubations to measure the rate of heterotrophic respiration and the ∆ 14 C of respired CO2 to assess C turnover utilization by microbes. While incubations provide an integrated assessment of microbial respiration and C turnover, soil sampling and preparation prior to incubation can result in artifacts due to the disruption of soil structure, roots, and microbial communities (Salomé et al 2010, Herbst et al 2016, Schädel et al 2020, Patel et al 2022. Comparisons between field-based and laboratory incubation studies show differences in gas flux rates (Williams et al 1998, Patel et al 2022, Risk et al 2008) and younger respired C in the field (Phillips et al 2013), suggesting that additional methods to assess microbial processes would be valuable.…”
Section: Introductionmentioning
confidence: 99%